The Profile of Navy Military Students with Superficial Fungal Foot Infections : A Descriptive Study - Medisika, Dhea; Prakoeswa, Cita Rosita Sigit; Sawitri, Sawitri; Hidayati, Afif Nurul; Utomo, Budi; Rahmadewi; Agung, Jeffrey; Ervianty, Evy (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Superficial fungal foot infection is an infectious disease caused by dermatophyte, Candida spp., and mold. Risk factors are thought due to poor personal hygiene, frequent used of closed shoes, and high physical activity. Purpose: Investigate the profile and the risk factors of superficial fungal foot infections in military students. Methods: This is a cross-sectional study. Inclusion criteria for this study were navy military students with lesions on their feet. Result: This study involved 194 students as the populations with 97 students as the sample of the study. The average age were 17-25 years old, and male students being the major. Erythema and scale were found in the plantar and interdigital pedis. Students with good personal hygiene were 81 students among 97 students (83,5%). Wearing closed shoes for > 8 hours were found in 72 students among 97 students (74.2%). Most of the students exhibit a high physical activity with an average score of 26,880 MET minutes/week. Positive KOH 20% and cultures were found in 30 students (30.9%). Negative KOH 20% and positive culture were found in 27 students (27.8%). Positive KOH 20% and negative cultures were found in 9 students (9.3%). Negative KOH 20% and negative fungal culture results were found in 31 students (31,9%). Mold was the predominant fungal type. Conclusion: The students had good personal hygiene. The average wears closed shoes for >8 hours. Mold was the predominant fungal type in this study.